Experimentally testing animal responses to prescribed fire size and severity - Tim S. Doherty; Daniel F. Bohórquez Fandiño; Darcy J. Watchorn; Sarah M. Legge; Chris R. Dickman (Conservation Biology, 2024)
Deserts are often highly biodiverse and provide important habitats for many threatened species. Fire is a dominant disturbance in deserts, and prescribed burning is increasingly being used by conservation managers and Indigenous peoples to mitigate the damaging effects of climate change, invasive plants, and land‐use change. The size, severity, and patchiness of fires can affect how animals respond to fire. However, there are almost no studies examining such burn characteristics in desert environments, which precludes the use of such information in conservation planning. Using a before‐after control‐impact approach with 20 sampling sites, we studied the outcomes of 10 prescribed burns of varying size (5–267 ha), severity, and patchiness to identify which variables best predicted changes in small mammal and reptile species richness and abundance. Three of the 13 species showed a clear response to fire. Captures increased for 2 species (1 mammal, 1 reptile) and decreased for 1 species (a reptile) as the proportional area burned around traps increased. Two other mammal species showed weaker positive responses to fire. Total burn size and burn patchiness were not influential predictors for any species. Changes in capture rates occurred only at sites with the largest and most severe burns. No fire‐related changes in capture rates were observed where fires were small and very patchy. Our results suggest that there may be thresholds of fire size or fire severity that trigger responses to fire, which has consequences for management programs underpinned by the patch mosaic burning paradigm. The prescribed burns we studied, which are typical in scale and intensity across many desert regions, facilitated the presence of some taxa and are unlikely to have widespread or persistent negative impacts on small mammal or reptile communities in this ecosystem provided that long unburned habitat harboring threatened species is protected.